Persepsi Digital Dependent terhadap Pemanfaatan Media Sosial dan Dampak Sosial Ekonominya - Rustiana (FISIP Universitas Atma Jaya Yogyakarta, 2018)
The aim of the study was to have empirical evidence of using social media, positive and negative impacts in the social and economic fields. A total of 179 respondents accounting students at one private university in Yogyakarta. Data had collected by questionnaire. Furthermore, the data had analyzed qualitatively by using descriptive statistics and item analysis. The implications are useful for digital dependent to be wise in using social media and aware of the positive and negative impacts. In addition, for companies and providers useful to analyze for the utilization of economic and social potential of social media.